Molecular Detection of Toxogenic Cyanobacteria Isolated from Tigris River in Baghdad City –Iraq - Zainulabdeen H. A. AL-Khafaji1, Ahmed S.Dwaish2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Algae and their contamination are being increasingly reported worldwide that cause a serious hazard to environmental and human health. Cyanotoxin was the most algal toxin reported to be produce by several orders of cyanobacteria. In 2017 cyanobacteria were isolated from fresh water of Tigris River and identified by light compound microscope as well as conventional PCR. Five isolates of cyanobacteria which successfully amplified a gene fragment from the phycocyanin shared by all cyanobacteria and only four isolates successfully amplified a gene fragment from the myc E belonged to microcystin. Our results concluded that PCR assay can be used for early detection of microcystin producing algae in fresh water that useful to stations responsible for the preparation of drinking water.